Sex Assignment and Re-Assignment in Patients with Steroid 5-Alpha Reductase Type Two Deficiency: The Psycho-Social, Religious and Cultural Challenges - Al-Jurayyan, Nasir A. M (British Journal of Healthcare and Medical Research, 2024)
Background: Steroid 5-alpha reductase type two deficiency (5 ARD 2) is a rare autosomal recessive disorder of sexual development. The lack of the enzyme, 5 -alpha reductase, that converts testosterone to dihydro testosterone, results in the external genitalia that may be appear atypical, normal to ambiguous external genitalia. Materials and Methods: A retrospective review of patients with 5 - alpha reductase type two deficiency were included. A coordinated multidisciplinary team of specialists were involved. Psych -social, cultural and religious factors were analyzed. Results: Four patients, from three families, among 12 patients, who were diagnosed with 5-alpha reductase type two deficiency in 46 XY disorders of sex development were wrongly assigned female sex at birth due to abnormal external genitalia. Their age ranged between birth to 12 years. Signs of virilization which occurred at 12years of age in one patient led to the diagnosis of the other. The other two patients were diagnosed during the investigation of ambiguous genitalia. The cultural factor was the commonest factor among others, influencing sex reassignment. Level of parental education had no role. Conclusion: Sex assignment remains one of the most clinically challenging and controversial in 46XY disorders of sex development (DSD), in particular that due to steroid 5-alpha reductase type two deficiency. Cultural factors are important, among psychosocial, and religious factors. Given the complexity of the disorder, it is also important to involve a multidisciplinary team of experts in the management.